THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND EMPLOYMENT ENGAGEMENT ON INNOVATIVE BEHAVIOR IN PT. SEMESTA INDOVEST SECURITY - Alviolenta, Yessy Vivi; Marsofiyati; Parimita, Widya (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of Transformational Leadership (X1) and Work Engagement (X2) on Innovative Work Behavior (Y) at PT Semesta Indovest Sekuritas. The research method used is a quantitative research method with a descriptive approach. The population in this study amounted to 125 employees. Based on the Slovin formula, the number of samples in this study is 95 respondents. The sampling technique used is purposive sampling technique. The data processing technique used in this study uses SPSS version 25. In this study, the data analysis techniques carried out included five stages, namely: (1) requirements analysis test; (2) classical assumption test; (3) multiple regression analysis test; (4) hypothesis testing; and (5) the coefficient of determination analysis test. The result shows that transformational leadership and work engagement affect the innovative work behavior of employees.